Determination of phenolic compounds in estuary water and sediment by solid-phase isotope dansylation coupled with liquid chromatography-high resolution mass spectrometry. Issue 11 (5th March 2021) - Xu, Wenxue; Hu, Yufeng; Wu, Minghuo; Miao, Enming; Zhou, Hao; Zhang, Xuwang; Zhan, Jingjing
Abstract : A method consisting of solid-phase isotope dansylation (derivatization with dansyl chloride) and liquid chromatography-high resolution mass spectrometry was developed for the quantitative analysis of phenols in environmental samples. Abstract : A method consisting of solid-phase isotope dansylation (derivatization with dansyl chloride) and liquid chromatography-high resolution mass spectrometry (LC-HRMS) was developed for the quantitative analysis of phenolic compounds (phenols) in environmental samples. A magnetic-HLB (hydrophilic lipophilic balanced) material was synthesized and applied as an adsorbent in magnetic solid-phase extraction (MSPE) for the enrichment of the analytical targets. Furthermore, with the solid-phase isotope labeling, the desalting and removal of labeling residuals could be simplified over conventional in-solution labeling. In addition to overcoming the matrix effect by isotope dansylation, the sensitivity for the analysis of phenols by LC-HRMS was remarkably improved by over 100-fold. The method was systematically verified, and good accuracy (86.5–104.9%) and precision (<8.6% and <11.4% for intra- and inter-day, respectively) were achieved for the tested 15 phenols. The limits of detection (LODs) of this method were estimated to be 0.2–5 ng L −1 and 5–100 ng kg −1 in estuary water and sediment samples, respectively. With this method, samples collected from the Daliao River estuary (Panjin, China) were analyzed. It was found that all of the targeted phenols were detected at concentrations ranging from unquantifiable to 485 ng L −1 (the total concentration of analytes found in each sample were in the range 822–957 ng L −1 ) and unquantifiable to 1368 ng kg −1 (the total concentration of analytes found in each sample were in the range 2251–2992 ng kg −1 ) in water and sediment, respectively.